1996
DOI: 10.1164/ajrccm.153.3.8630580
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and mortality in chronic obstructive pulmonary disease.

Abstract: The role of nutritional status in the prognosis of subjects with severe chronic obstructive pulmonary disease was studied in a cohort of Canadian men and women followed for 3 to 5 yr. A total of 348 subjects who were recruited for a study of negative pressure ventilation were evaluated for lung function and body weight, and a subset who entered hospital for the study (n=184) had baseline measures of diffusing capacity, maximal inspiratory and expiratory mouth pressure (PImax and PEmax), and blood gases. Predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
180
3
15

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(213 citation statements)
references
References 21 publications
15
180
3
15
Order By: Relevance
“…32 The results of this study are in line with those of previous reports showing that body weight depletion is related to a decreased exercise performance in COPD patients. [8][9][10][11][12] Our patients with low FFM showed a significant reduction in aerobic capacity both at peak of exercise and at AT. In our study, depleted and nondepleted patients did not differ in both resting spirometry and lung volume measurements and in operational volumes measured during maximal exercise.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…32 The results of this study are in line with those of previous reports showing that body weight depletion is related to a decreased exercise performance in COPD patients. [8][9][10][11][12] Our patients with low FFM showed a significant reduction in aerobic capacity both at peak of exercise and at AT. In our study, depleted and nondepleted patients did not differ in both resting spirometry and lung volume measurements and in operational volumes measured during maximal exercise.…”
Section: Discussionmentioning
confidence: 63%
“…7 Importantly, the reduction in FFM may also contribute to impairment of exercise capacity in these patients. Earlier studies [8][9][10] have reported a significant correlation between body weight and maximal exercise capacity in COPD patients. Notably, the FFM was found to be strictly related both to submaximal 11 and maximal 12 exercise performance in these patients.…”
Section: Introductionmentioning
confidence: 93%
“…In end-stage lung diseases, lean body mass seems to be a better tool to assess nutritional depletion and monitoring this parameter in lung transplant candidates is recommended. If mortality is considered, the study confirms that nutritional status per se is of value to predict survival while awaiting LT [4,5,13,16,17]. In the postoperative course, nutritional depletion increases the risk of death, mainly in CF patients, as shown by different groups [5,6,13] but not by others [4].…”
Section: Discussionmentioning
confidence: 74%
“…m -2 [4,5,7,13]. In COPD patients, the prevalence of nutritional depletion increases with the degree of bronchial obstruction [8,10,14,16,17], the level of hypoxaemia [8,15] and the subtype of COPD, emphysema patients being more depleted [14]. Hypoxaemia per se modifies muscle mass through a sharp decline in protein synthesis so that oxygen supply can adapt to demand [18].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that protein requirements in elderly individuals may in fact be higher (1.0 g/kg body weight/d) than current recommendations (0.86 g/kg body weight/d) (Campbell et al, 1994). The preservation of lean body mass in heavier subjects may also be a factor in the better survival of heavier COPD patients compared to those who are at what is generally accepted as normal body weight (Chailleux et al, 1992;Gray-Donald et al, 1996).…”
Section: Discussionmentioning
confidence: 99%